(untitled) (Research, Society and Development, 2018)
This study aims to report an experience of qualification of the university extension in the health area through contemporary teaching strategies. It is an experience report, descriptive and exploratory, with a qualitative approach. The field of study for the present study was a university extension course. It was in this thematic context in which the experience of applying two teaching strategies was inserted, being Brainstorming and the Case Study. Some difficulties were identified, such as the teacher’s insecurity in using strategies in a differentiated teaching space, however, they were overcome in the sense that the strategies were well accepted by the class, generating the expected results for professional qualification.